1999
DOI: 10.1063/1.478412
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of cyclopentadienyl and substituted cyclopentadienyl radicals in small clusters. II. Cyanocyclopentadienyl with polar solvents

Abstract: Clusters of the cyanocyclopentadienyl (CNcpd) radical and several polar solvent molecules (e.g., CF2H2, CF3H, CF3Cl, CH3Cl, ROH, H2O) created in a supersonic jet expansion are studied by laser induced fluorescence and hole burning spectroscopies. Lennard-Jones–Coulomb atom–atom potential energy calculations are employed in combination with ab initio calculations to aid in the interpretation of the observed spectra and to understand the nature of the radical polar solvent solvation behavior. The calculations pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…[12][13][14][15][16] After the ESR observations in condensed phase, the spectroscopy of the isolated radical has been reported. [17][18][19][20][21][22][23][24][25] After pioneering work by Liehr, 26 theoretical calculations have been piled up. [27][28][29][30] quite excellent, cyclopentadienyl radical is a good target for our calculation of the vibronic coupling.…”
Section: ͑2͒mentioning
confidence: 99%
“…[12][13][14][15][16] After the ESR observations in condensed phase, the spectroscopy of the isolated radical has been reported. [17][18][19][20][21][22][23][24][25] After pioneering work by Liehr, 26 theoretical calculations have been piled up. [27][28][29][30] quite excellent, cyclopentadienyl radical is a good target for our calculation of the vibronic coupling.…”
Section: ͑2͒mentioning
confidence: 99%
“…Most of this work centered on the vibrational structure revealed by theà 2 A 2 ←X 2 E 1 electronic transition. [6][7][8][9][10] This work was supplemented by rotationally resolved work [11][12][13] on this transition's origin band and photo-detachment experiments 14 on C 5 H −…”
Section: Introductionmentioning
confidence: 99%
“…These studies are useful because solvation is important for the understanding of the observed substituent effects on the spectra, structure, and chemistry of the phenoxy radical in water . Moreover, the differential solvation of phenol and phenoxy radical can be related to the energetics of the phenol O−H homolytic bond dissociation and to chemical reactivity in solution. , Modeling of solvent effects by “microsolvation” in clusters has also been employed to discuss the structure and energetics of several radical species including the methoxy radical, cyclopentadienyl radicals, and the 2,5-lutidyl radical …”
Section: Introductionmentioning
confidence: 99%
“…19 Moreover, the differential solvation of phenol and phenoxy radical can be related to the energetics of the phenol O-H homolytic bond dissociation and to chemical reactivity in solution. 6,[20][21][22] Modeling of solvent effects by "microsolvation" in clusters has also been employed to discuss the structure and energetics of several radical species including the methoxy radical, 23 cyclopentadienyl radicals, [24][25][26] and the 2,5-lutidyl radical. 27 Statistical mechanics computer simulations can provide data on the structural and thermodynamic properties of liquids and solutions (see Dufy and Jorgensen for a recent review).…”
Section: Introductionmentioning
confidence: 99%